Patients with Autism Spectrum Disorders: Strategy for Orthodontic Care - Swati Saraswata Acharya; Satyabrata Patnaik; Smruti Bhusan Nanda (Journal of Clinical and Diagnostic Research, 2018)
Autism Spectrum Disorders (ASD) are developmental behavioural defined neuropsychiatric disorders that start in early childhood involving social abnormalities, language-communication deficit play, and restricted behaviour. There has been an increasing appreciation that other fields or domains of neurologic and cognitive functioning beyond this diagnostic triad are associated in this syndrome. With the increased prevalence of children having these disorders, orthodontists have one or two autistic patients in their practice. Orthodontic requirements constitute only a small fraction of the overall need of these patients. This review focuses about ASD as an amnestic abnormality of memory, unique features of memory dysfunction with neurobiologic context, mechanisms and comprehensive knowledge pertaining to orthodontic treatment considerations in these patients.